Role of City Mobile Library in Advancing Education in Pekanbaru City - Raja Syamsidar, Yuhelmi, Rismayeti, Evizariza, (Opción, 2019)
This study aimed to determine the role of the mobile library at the city library in advancing education in Riau province via both quantitative and qualitative research methods. Respondents in this study were all staff in the Mobile library program. The results of this study showed that the provision of library collections around was still lacking and needed addition. It can be concluded that the four variables examined the role of Mobile Library in advancing education in the city of Pekanbaru is still lacking in providing collections that match with visitor’s interest.